UPAYA MENINGKATKAN PRESTASI BELAJAR IPA DENGAN METODE PEMBELAJARAN PENEMUAN (DISCOVERY) - Imam Rosyidi (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
The purpose of this action research was to describe (1) the increase of the students’ achievement after the implementation of discovery learning and (2) the effect of students’ motivation after the implementation of discovery learning. The study used action research with three cycles. cycles consisted of four phases: design, activities and observations, reflections, and revision. The goal of the study was the forth graders of the first state elementary school of Paciran in the academic year of 2016/2017 in the first Semester . The data obtained in the form of a formative test results, observation sheet teaching and learning activities. From the analysis found that the students’ achievement had increased from the first cycle to the third cycle, namely, the first cycle (70.00%), the second cycle (85.00%), the third cycle 95.00%). The result showed that the use of the discovery learning gave a positive effect on the students' motivation so that it could be used as an alternative in learning science.